Manifestation and Benefits of Voice among Informal Sector Entrepreneurs: Experiences from Jua Kali Associations in Western Kenya - Juepner, Anne Gertraude; McCormick, Dorothy; Ng'ethe, Njuguna (Advances in Social Sciences Research Journal, 2018)
This article explores how voice manifests itself among informal sector entrepreneurs and the benefits of voice based on a case study of Jua Kali Associations in Homa Bay Town in Western Kenya using Hirschman's concept of voice, loyalty and exit as the theoretical frame [30] based on data generated and analysed through a qualitative research design. The study’s findings show that voice among entrepreneurs in the informal sector constitutes expression of interests, needs and priorities which vary among the members of the JKAs examined and are shaped by different factors such as their socio-economic profile, the nature of their business and the environment the women and men entrepreneurs operate in. Expressions of voice can be in a continuum ranging from soft voice used by individuals in the private sphere to loud voice and organised protests in the public domain. The study further shows that among this group of people, voice can have multiple benefits; key among them contributions to their social protection, and economic and political empowerment; voice can also contribute to enhanced self-esteem of individual entrepreneurs. The former benefits can be realised when Jua Kali Association members are organised and have systematic and prolonged engagement with their respective audience.